Estudio de factibilidad para la creación de una caja de ahorro en la compañía de taxi ejecutivo SURAMEX S.A de la ciudad de Loja - Aguirre Meneses, Brigitte Fernanda (2019)
The present thesis called “Feasibility Study for the creation of a Savings Bank in the Compañía de Taxi Ejecutivo Suramex S.A. of the City of Loja” aims to incentivize the culture of savings and grant credits easily and immediately to partners of the Compañía de Taxi Suramex, increasing new growth opportunities to improve the economy and quality of life of the partners, through a proprietary source of resources that provides financing to their daily activities; for which it was implemented on the basis of four specific objectives: market, technical, legal-administrative and economic-financial study. To meet the proposed objectives, different methods and techniques applicable to each study were used, based on methods: deductive, inductive, analytical, statistical and technical methods such as surveying, observation and bibliographic compilation. With regard to the results, the first objective carried out the market study, through the application of surveys to the partners of the taxi company to know their interest and degree of acceptance of the Savings Bank, in effect , it was determined that there is a demand from 42 partners; the second objective produced the technical study where it was established that the company's offices are the most suitable location for the box to provide its services, as well as the necessary requirements and processes; in the third objective, the legal-administrative study was implemented in which the structure of the savings bank, its legal status and rules of procedure were implemented, the same ones that will manage its operation; the fourth objective developed was the economic-financial study where the investment needed to launch the project was determined, the financing will be obtained through mandatory savings by the partners, as well as the costs were analyzed, income, cash return and cash flow to subsequently use financial assessment tools such as net present value, internal rate of return, profit-cost ratio and capital recovery period. In conclusion, it was determined that the project is feasible according to the results obtained, guaranteeing sustainability to the Taxi company and generating economic and social development.